Eksploitasi Anak Dalam Perspektif Hukum Pidana Islam Di Kota Rantauprapat - Ritonga, Dhea Kartika (JURNAL LEGISIA, 2024)
Child exploitation is arbitrary action and discriminatory treatment of children carried out by the community or family with the aim of forcing the child to do something without regard to the child's rights such as physical and mental development. Here we want to see the form of child exploitation crimes that have developed to the smallest regions including the city of Rantauprapat. Islamic criminal law regulates child exploitation. The purpose of this study is to determine the views of Islamic criminal law and the form of crime regarding child exploitation in Rantauprapat. The research approach used is normatipe-empirical with descriptive nature. Primary data conducted by interview is supported by secondary data. The results of this study show the huge impact on children who are exposed to child exploitation has a very fatal impact on the physical and mental health of children. The crime of exploitation of children is carried out in various forms of activities which basically aim to deprive children of their rights and freedoms to grow and develop in a reasonable environment. The crime of child exploitation can be considered as a serious criminal offense, therefore law enforcement authorities are expected to strictly enforce and impose strict penalties for perpetrators of acts of exploitation of children.